Cell metabolism-based optimization strategy of CAR-T cell function in cancer therapy - Li, Wenshuai; Pan, Xuanxuan; Chen, Lirong; Cui, Haoshu; Mo, Shaocong; Pan, Yida; Shen, Yuru; Shi, Menglin; Wu, Jianlin; Luo, Feifei; Liu, Jie; Li, Na (Frontiers in Immunology, 2023)
Adoptive cell therapy (ACT) using chimeric antigen receptor (CAR)-modified T cells has revolutionized the field of immune-oncology, showing remarkable efficacy against hematological malignancies. However, its success in solid tumors is limited by factors such as easy recurrence and poor efficacy. The effector function and persistence of CAR-T cells are critical to the success of therapy and are modulated by metabolic and nutrient-sensing mechanisms. Moreover, the immunosuppressive tumor microenvironment (TME), characterized by acidity, hypoxia, nutrient depletion, and metabolite accumulation caused by the high metabolic demands of tumor cells, can lead to T cell "exhaustion” and compromise the efficacy of CAR-T cells. In this review, we outline the metabolic characteristics of T cells at different stages of differentiation and summarize how these metabolic programs may be disrupted in the TME. We also discuss potential metabolic approaches to improve the efficacy and persistence of CAR-T cells, providing a new strategy for the clinical application of CAR-T therapy.